(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
During ontogenetic development, insects can undergo quite drastic changes (metamorphosis) until the adult stage is reached. A substantial part of this development in one group of Insecta, Holometabola, takes place during the pupa stage. Despite the pupa being recognised as an important phase, rather few depictions of pupae exist in the literature. We report here the first find of a fossil pupa of the lacewing group Mantispidae. The specimen represents an exuvia and is enclosed in Ukrainian Rovno amber, Eocene in age (c. 35–40 million years). We review the entire record of extant pupae of Mantispidae depicted in the literature or in online image repositories. With the aid of elliptic Fourier analysis, we compare the outline of the femur of the foreleg (raptorial appendage in the adults) of pupae and adults of Mantispidae. The pupae are all very similar concerning the femur, while the adults show a larger morphological diversity, particularly the extinct forms. Furthermore, our results indicate that the forelegs do not become increasingly complex throughout ontogenetic stages, but instead undergo an indirect development. According to the low variation in morphology seen in the pupa stage in Mantispidae, it is plausible that it represents a phylotypic stage for the group, i.e. a phase characterised by a significantly lower variability than other stages.